My way : essays on moral responsibility - Fischer, John Martin, 1952- (Oxford University Press, 2006)
A collection of John Martin Fischer's essays on free will and moral responsibility. Fischer's overall framework contains an argument for the contention that moral responsibility does not require free will in the sense that implies alternative possibilities and a sketch of a comprehensive theory of moral responsibility.